Arctic cruise of H.M. Submarine Ambush , 1948 - Davies, A. G. (Polar Record, 1950)
On 12 February 1948, H.M. Submarine Ambush sailed from Rothesay, Isle of Bute, to carry out a prolonged investigation into the effects of “snorting” in rough weather and conditions of extreme cold. H.M. Submarine Ambush , built since the end of the war, is a vessel of some 1350 tons surface displacement, 287 ft. long, embodying a large number of the latest developments including “snort” and radar. Apart from scientific measuring instruments, no special features were installed in the ship and her company, five officers and sixty men, was the normal crew with the addition of Surgeon Lieutenant-Commander W. H. Davidson, R.N., as observer for the Royal Naval Physiological Laboratory, and an assistant. No changes were made and no men were specially selected for the mission.